2016
DOI: 10.1021/acscatal.5b02657
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Methane Activation and Oxide Catalyst Reducibility and Its Implications for Oxidative Coupling

Abstract: We investigate methane activation over a range of metal-oxide surfaces. Density functional theory calculations are used to correlate the C−H bond activation energy to the surface reducibility (oxygen vacancy formation energy, work function). The correlation includes several reducible and nonreducible metal-oxides, doped CeO 2 , doped TiO 2 , ZnO, and doped MgO, and also holds for various oxidation states of TbO x , different surface facets of TiO 2 , and variation of Hubbard U parameter for CeO 2 . We find a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
138
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(158 citation statements)
references
References 68 publications
(124 reference statements)
1
138
0
2
Order By: Relevance
“…It can be expected that oxygen species with moderate activity, which was evolved via the simple hetero-exchange mechanism, plays a beneficial role in CH 4 activation (Kumar et al, 2016), leading to the selective oxidation to C 2 H 6 /C 2 H 4 . Taking into account the fact that the temperature for the evolution of 16 O 18 O and 16 O 2 was significantly lowered by addition of CeO 2 into Y 2 O 3 (Figure 9), we can conclude that the catalytically role of CeO 2 in the OCM reaction is to promote the formation of active oxygen species via the simple hetero-exchange mechanism.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be expected that oxygen species with moderate activity, which was evolved via the simple hetero-exchange mechanism, plays a beneficial role in CH 4 activation (Kumar et al, 2016), leading to the selective oxidation to C 2 H 6 /C 2 H 4 . Taking into account the fact that the temperature for the evolution of 16 O 18 O and 16 O 2 was significantly lowered by addition of CeO 2 into Y 2 O 3 (Figure 9), we can conclude that the catalytically role of CeO 2 in the OCM reaction is to promote the formation of active oxygen species via the simple hetero-exchange mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…The OCM reaction proceeds via the formation of methyl radicals formed by the reaction of methane with active oxygen species and subsequent coupling the methyl radicals (Dubois and Cameron, 1990). Therefore, designing the catalyst surface to create the active oxygen species such as O − , O22-, and O 2− for the OCM reaction must be the important strategy to develop highly active catalysts (Kumar et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…A number of descriptors have been proposed as possible descriptors of oxygen reactivity in metal oxides, which include the energetic quantities E Hads and E vac and electronic ones such as Bader charge and work function . E Hads and E vac show strong linear correlations with a low mean absolute error (MAE) of 0.16 eV and R =0.93 (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…in VASP using a Hubbard parameter U =2 eV for the Co atom as used in previous studies . Theoretical studies have shown that the change of the U value does not disturb the linear relationships studied in this work . The Perdew–Burke–Ernzerhof (PBE) form of the generalized‐gradient approximation (GGA) was used for electron exchange and correlation.…”
Section: Methodsmentioning
confidence: 99%
“…Previous study discovered that the activity property of RMOs can be altered dramatically and reversibly by supplying or removing oxide anions, which was attributed to variation in the work function of these catalyst materials . Kumar et al investigated the relationship between methane activation energy and RMO work function and reported a linear correlation, which however was rough with significant data point scattering and relatively large mean absolute error . Thus a good theory that identifies RMO descriptor parameters to better describe the activity property is needed.…”
Section: Figurementioning
confidence: 99%